Puerto Rico - Di Duca, Marc; Garcia, Amaya; Garry, John; Ramos, Vanessa (Lonely Planet guidebooks., 2023)
Lonely Planet's Puerto Rico is our most comprehensive guide that extensively covers all the country has to offer, with recommendations for popular and lesser-known experiences. Follow Old San Juan's labyrinthine laneways, laze on the sand at Playa Flamenco, or kayak into the bioluminescent bay at Vieques; all with your trusted travel companion.